Atendimento educacional especializado (AEE) e ensino regular: avanços, limites e desafios na prática docente do município de Bragança-Pa - MOURA, Ana Paula Abreu (2021)
The present study started from the following question: what are the advances, limits and challenges in teaching practice in the ESA and in the regular teaching of municipality of Bragança-PA? In this sense, the objective is to study the advances, limits and challenges in the teaching practice of ESA and regular education in the municipality of Bragança-PA, as well as to identify the main pedagogical practices developed in the school environment, concerning students with disabilities and their inclusion in the school. teaching and learning process, and analyzing the process of Specialized Educational Attendance at the Bragança public school, were the ones that demanded the corpus of the present study. Methodologically, the study printed the qualitative approach, with the questionnaire instrument guarded with semi-structured questions. In addition, the analysis took place through the interpretation of content analysis, as well as documentary analysis. The main results indicate that there is a teaching practice focused on the care of students with disabilities, although there are limitations due to the absence of family support, limited training to special education, as well as the absence of physical space and materials adapted to each disability. Conclusively, he says that the Specialized Educational Care occurs in public schools in Bragança with limitations that are beyond the teaching practice, where the limitations are for other issues.